EFFECT OF LIQUID NITROGEN MINERAL FERTILIZER ON PLANT GROWTH AND DEVELOPMENT, MAINTAINING FERROCENE FORMATIONS IN ITS COMPOSITION (Scientific journal of the Fergana State University, 2023)
The article provides specific scientific and practical results for the development of fertilizers containing nitrogen, phosphorus, potassium, and certain trace elements necessary for agricultural needs in the Republic, increasing the volume of competitive products and expanding their range, as well as data on the synthesis of water-soluble biologically active compounds of ferrocene derivatives and their basis obtaining liquid fertilizers containing trace elementsIn addition, biostimulant properties of new liquid nitrogen fertilizers obtained basis on water-soluble salts of CAS and ferrocene derivatives were determined in field practice in the tests carried out in the growth and development of grain and wheat plants, as well as the optimal standards for the application of new liquid nitrogen fertilizers for these plants. According to the results of the phenological observation in 2019-2021, the fact that along with the physiological processes in the plant treated with liquid fertilizer "Farben-potassium", biochemical processes were also optimal, the results of field tests carried out by additional feeding of liquid nitrogen fertilizers through the leaf of wheat and hemp plants. In addition, the resistance of the plant to harmful insects has increased, and the results of field tests conducted by additional feeding of liquid nitrogen fertilizers through the leaves of wheat and cotton plants have been cited.